Structural-functional Variability in Pectin and Effect of Innovative Extraction Methods: An Integrated Analysis for Tailored Applications. Issue 4 (19th May 2023) - Khubber, Sucheta; Kazemi, Milad; Amiri Samani, Sara; Lorenzo, Jose M.; Simal-Gandara, Jesus; Barba, Francisco J.
ABSTRACT: The pectin from different sources varies in view of major domains (homogalacturonan HG, rhamnogalacturonan, RG-I or RG-II) and extent of esterification determining major functional properties such as gelling, viscosifying, or stabilizing. The mechanism of sustainable extraction methods (ultrasound, US; microwave, MW; pulsed electric field, PEF; ultra-high pressure, UHP; subcritical water, SW) affects pectin. For retained structural features and functionality, lower power and temperature for US/MW/PEF may be preferred, while UHP and SW does not impart significant changes in pectin. For tailored applications, it is important to segregate the extraction methods as per the sources to achieve typical structure and functionality of pectin. Abbreviations HG: homogalacturonan; RG: rhamnogalacturonan; US: ultrasound; MW: microwave; PEF: pulsed electric field; UHP: ultra-high pressure; SW: subcritical water; GalA: galacturonic acid; HG: homogalacturonan; NS: neutral sugars; XG: xylogalacturonan; DE: Degree of esterification; HMP: high-methoxyl pectin; LMP: low-methoxyl pectin; EZA: enzyme-assisted; SAM: S-Adenosylmethionine; HM: high-methoxyl; LM: low-methoxyl; Mw : molecular weight; L-Rha: L-rhamnose; L-Ara: L-arabinose; D-Gal: D-galactose; WHC: water holding capacity; EA: emulsifying activity; ES: emulsion stability; O/W: oil/water; OHC: oil holding capacity; DPPH: 2, 2-diphenyl-1-picryl-hydrazyl; BHT: butylated hydroxy toluene; GAE: gallic acid equivalent; CH: conventional heating; HWE: hot water extraction; UMAE: ultrasound-microwave-assisted extraction; MAE: microwave-assisted extraction; UAE: ultrasound-assisted extraction; HHP: high hydrostatic pressure.